Measurement, reporting and verification of climate-smart agriculture: Change of perspective, change of possibilities? - Rosenstock, Todd S.; Wilkes, Andreas; Nowak, Andreea C.; Akamandisa, Vincent M.; Bondo, Austin; Kimaro, Anthony A.; Lucas, Irene; Makoko, Kondwani; Masikati, Patricia; Malozo, Mponda; Morongwe, Sepa; Ngwira, Gomezyani; et al. (2018)
The World Agroforestry Centre (ICRAF), Unique Forestry and Land Use and Vuna have been working with stakeholders in four countries in eastern and southern Africa (Tanzania, Malawi, Zambia and Zimbabwe) to assess the current state of national CSA M&E and to set out country-specific roadmaps for developing systems for monitoring and reporting on CSA. The project took a country-driven approach to documenting stakeholders’ information needs, exploring how to build on and align with existing M&E systems and international reporting frameworks, and encouraging cross-country comparisons. Though the research was grounded in southern Africa, these lessons are applicable to CSA and other topic-driven initiatives (such as land restoration and the Bonn Challenge) across similar environments and social contexts on the continent and around the world. Here we detail three key findings from the assessment.